THE ORETICAL BASICS OF ENSURING FOOD SECURITY IN UZBEKISTAN - Baymuratova Gulirayhon Tursunbaevna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article reveals the importance, essence and theoretical foundations of ensuring food safety. Based on the analysis of socio-economic changes and measures implemented to ensure food safety in Uzbekistan during the years of independence, it contains relevant proposals for strengthening the country's food safety.